1993
DOI: 10.1099/00221287-139-6-1125
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella reference collection B (SARB): strains of 37 serovars of subspecies I

Abstract: A reference collection of 72 strains representing 37 serovars of Salmonella subspecies I has been established for use in research on genetic and phenotypic variation in natural populations. Included are isolates of the host-adapted serovars S. choleraesuis, S. dublin, S. gallinarum, S. paratyphi A , S. paratyphi B, S. paratyphi C, S. pullorum, S. sendai, S. typhi and S. typhisuis, as well as strains of S. enteritidis, S. typhimurium, and other commonly recovered serovars with broad host ranges. The isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
186
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(198 citation statements)
references
References 23 publications
10
186
2
Order By: Relevance
“…The results of tests for biochemical activities, 16S rrn profile, rate of phase change and presence of IS200 are recorded in Table 1, in which strains are placed in groups according to our results. These indicated reassignment of two SARB strains to serotypes other than those shown [6].…”
Section: Screening Of Strains and Assignment To Groupsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of tests for biochemical activities, 16S rrn profile, rate of phase change and presence of IS200 are recorded in Table 1, in which strains are placed in groups according to our results. These indicated reassignment of two SARB strains to serotypes other than those shown [6].…”
Section: Screening Of Strains and Assignment To Groupsmentioning
confidence: 93%
“…Some of these strains, indicated with the suffix K in Table 1, are from the Kauffmann collection and may be considered the ' type ' strains of the group concerned. We examined all the strains of antigenic formula O6,7 : c : 1,5 included in the SARB collection [6]. This collection includes, for many serotypes, one strain of the electrotype most commonly encountered in that group and one representative of one or more of the less common electrotypes in the serotype.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…This group of serotypes includes the swine-adapted Choleraesuis, the swine-restricted serotype Typhisuis, and the human-restricted Paratyphi C. Typhisuis has been reported to be polyphyletic by MLEE analysis, with clone Ts3 genotypically related to Decatur (also with serotype O: 6,7 : c : 1,5) and very different from Ts1 and Ts2 [24,37]. However, in a more recent study based on ribotyping, IS200 fingerprinting, and biochemical analysis, Ts3 was reclassified as Decatur [38].…”
Section: Taxonomy and Population Geneticsmentioning
confidence: 99%
“…Thus, Typhisuis is strongly homogeneous and supports the argument that HR serotypes are less diverse than those that are pathogenic for a wide variety of animal hosts. Furthermore, Typhisuis appeared to be allied to Choleraesuis and to certain clones of Paratyphi C [37,38]. It has been suggested that these serotypes evolved from a common ancestor that was already capable of systemic infection and adapted to swine and that the acquisition of the Vi antigen by Paratyphi C allowed this serotype to adapt to humans [24].…”
Section: Taxonomy and Population Geneticsmentioning
confidence: 99%
See 1 more Smart Citation